European Transport Policy and Cohesion - An Assessment by CGE Analysis - Johannes Bröcker; Nils Schneekloth (European Regional Science Association (ERSA), 2005)
This paper studies the spatial impact of two main aspects of European transport policy, namely infrastructure investments and pricing. In its "White Paper: European Transport Policy for 2010: Time to Decide" the European Commission has laid down a comprehensive programme of transport policy within the EU, aiming at increasing the efficiency of the transport industry, developing the so-called trans-European infrastructure network and bringing the prices of transport services closer to the true marginal social cost. It is an important political issue whether the policy will enhance spatial cohesion in Europe or run counter the objective of a balanced economic development in the entire area of the EU. For one thing this is because spatial development objectives are themselves prominent goals among the catalogue of objectives to be attained by transport policy. Particularly infrastructure investments which are co-financed by the structural funds, are regarded a means of regional policy supporting less favoured regions. Furthermore, transport policies motivated by efficiency or environmental reasons may have undesired regional side effects, that could generate political backlash, unless one offers some compensation. The spatial impact of the two named policies is studied with the help of a spatial computable general equilibrium model, called CGEurope. It is a static model with a large number of regions covering the whole area of the EU including the new member states, plus neighbouring countries, some of them also subdivided by regions. Regions interact by trade flows. Interregional trade is costly, with trade costs depending inter alia on the state of infrastructure and on gasoline prices and infrastructure charges. Transport policies are simulated by varying the costs of transport and quantifying the impact on the welfare of households brought about by changes in goods and factor prices. We develop a series of policy scenarios and evaluate their impact an spatial equality or inequality using a whole bundle of indicators of spatial inequality. The paper documents theses scenarios, explains the modelling framework in brief, discusses the inequality indicators to be used and maps and tabulates the main results.
Keywords: 330